2016
DOI: 10.1038/srep31201
|View full text |Cite
|
Sign up to set email alerts
|

Localized Down-regulation of P-glycoprotein by Focused Ultrasound and Microbubbles induced Blood-Brain Barrier Disruption in Rat Brain

Abstract: Multi-drug resistant efflux transporters found in Blood-Brain Barrier (BBB) acts as a functional barrier, by pumping out most of the drugs into the blood. Previous studies showed focused ultrasound (FUS) induced microbubble oscillation can disrupt the BBB by loosening the tight junctions in the brain endothelial cells; however, no study was performed to investigate its impact on the functional barrier of the BBB. In this study, the BBB in rat brains were disrupted using the MRI guided FUS and microbubbles. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
75
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 49 publications
5
75
1
Order By: Relevance
“…Previous work by Cho et al . has shown that FUS induces a downregulation in immunodetection of P-gp 24 hrs post-sonication43. Results presented here are consistent with this finding, as there was a significant reduction in Abcb1a gene expression 6 hrs following FUS.…”
Section: Discussionsupporting
confidence: 91%
“…Previous work by Cho et al . has shown that FUS induces a downregulation in immunodetection of P-gp 24 hrs post-sonication43. Results presented here are consistent with this finding, as there was a significant reduction in Abcb1a gene expression 6 hrs following FUS.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, several studies suggested that FUS may not restrict to the "physical" disruption, but might also impact BBB physiology [26]. Using similar conditions to ours, Cho and colleagues reported a decrease in ABCB1 expression at the BBB of the sonicated area, 24 h after FUS [28]. Aryal et al, confirmed this observation and showed that the effect was maximum 48 h post FUS (~50% decrease) [27].…”
Section: Discussionsupporting
confidence: 73%
“…It can be hypothesized that ABC-transporter function may be modulated by BBB integrity. Recent studies have reported an impact of FUS-induced BBB disruption on the rat microvascular transcriptome [26] and a delayed decrease in ABCB1 expression in the sonicated area, 24 to 48 h after FUS [27,28]. This suggests that erlotinib, which brain distribution is mainly governed by ABC-transporter mediated efflux at the BBB, may benefit from the immediate and/or delayed impact of FUSinduced BBB disruption as a strategy to locally improve its brain delivery.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth noticing that differing events regarding the modulation of the protein by the presence of uid ow have been reported not only in intestinal models. For instance, a study by Garcia-Polite et al demonstrated that the protein activity had a peak when endothelial cells were subjected to a shear stress of 1 Pa and that it decreased for a shear stress of 4 Pa (40); while there is a contrasting hypothesis that P-gp is down regulated in arterioles of rat brain in response to a higher shear stress (41,42). Nevertheless, the shear stress provided by the ow in the present study is below the mentioned ranges and suggests that these cells are highly sensitive to even low levels of mechanical stimuli.…”
Section: Discussionmentioning
confidence: 99%